Slicing the Market: STP Analysis of Fast-Food Purchase Behavior in Makassar - Muhammad Ilham Wardhana Haeruddin (PT Maju Malaqbi Makkarana, 2026)
This study seeks to examine the impact of segmentation, targeting, and positioning on consumer purchasing decisions at fast food establishments in Makassar City. This study employs a quantitative methodology utilising a survey technique through questions administered to 180 respondents selected via the Hair formula. The data were subjected to validity tests, reliability tests, and multiple linear regression to assess the partial and simultaneous effects among factors. The research findings indicate that segmentation and targeting exert a favourable and considerable influence on purchase decisions, however positioning does not demonstrate a meaningful partial effect. The three STP variables concurrently exert a substantial impact on customer purchase decisions. These findings confirm that effective segmentation and targeting methods are more influential in improving purchase decisions than placement in the context of fast food restaurants in Makassar.